2016
DOI: 10.1093/afraf/adw019
|View full text |Cite
|
Sign up to set email alerts
|

The asset debates: How (not) to use asset indices to measure well-being and the middle class in Africa: Table 1

Abstract: Asset indices are ubiquitous in the debate about wellbeing in African countries, not least because of the paucity of traditional household income and expenditure data. Indeed, asset data have fuelled the creation of a new, more optimistic picture of wellbeing in Africa, where both income and the middle class are growing fast. This is the first review of the use of asset indices for African countries. Readers are guided through key debates over the use of asset data, including the use of assets to measure trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…A heated debate over whether an African growth "miracle" occurred in the 1990s was sparked due to comparisons of well-being based on asset indices, which had grown considerably, with well-being based on national accounts, which had not. Further analysis of this mystery revealed that factors such as new cheap imports of household durables from Asia and the tendency of household asset prices to drop over time were driving this discrepancy, but to this day there are many dissenting opinions and uncertainty over whether welfare has truly improved (Johnston and Abreu 2016).…”
Section: Income Consumption and Wealth Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A heated debate over whether an African growth "miracle" occurred in the 1990s was sparked due to comparisons of well-being based on asset indices, which had grown considerably, with well-being based on national accounts, which had not. Further analysis of this mystery revealed that factors such as new cheap imports of household durables from Asia and the tendency of household asset prices to drop over time were driving this discrepancy, but to this day there are many dissenting opinions and uncertainty over whether welfare has truly improved (Johnston and Abreu 2016).…”
Section: Income Consumption and Wealth Indicesmentioning
confidence: 99%
“…The mechanism for this urban divide can largely be attributed to a combination of rural households having fewer assets, more commonly owned assets, and agricultural assets often being assigned negative factor loadings. As one illustrative example, there is a village in Guinea-Bissau where (unlike the rest of the country) portable gas stoves are highly desired, and therefore behave as a normal good, 5 but because that village is relatively poor compared to other villages, the wealth index scoring of gas stoves is negative (Johnston and Abreu 2016). Similarly, owning a common asset will usually imply a negative scoring, which could perversely rank a household as poorer than one lacking the asset at all (Wittenberg and Leibbrandt 2017).…”
Section: Urban-rural Considerationsmentioning
confidence: 99%
“…Our data come from a variety of social, economic and environmental settings, all of them rural, but all primarily agricultural (not pastoral or fishing communities). We undertook this work in order to explore the recommendations made by Johnston and Abreu (2016) as to the geographical limits of asset indices and the need for asset indices that reflected local understandings of wealth.…”
Section: Resultsmentioning
confidence: 99%
“…That research has aroused some controversy (Harttgen, Klasen, and Vollmer 2013, and see our discussion of this in paper Brockington et al 2018). But, for the purposes of the present discussion, the most important criticism is that made by Johnston and Abreu (2016). They observe asset indices are built on a core assumption (not empirically derived observation) that assets correlate with wealth.…”
Section: Defining Wealth and Povertymentioning
confidence: 88%
See 1 more Smart Citation